SHARING KITAB SUCI DAN KATEKESE UMAT BAGI UMAT KBG ST. PADRE PIO DI PAROKI SANTA MARIA FATIMA, CANCAR - Nesiria Sulfa Dima; Fransiska Salestin Atipati; Donata Hawa Burga; Fransiska Widyawati (Randang Tana - Jurnal Pengabdian Masyarakat, 2023)
This article describes the Community Service activities carried out by the PkM Team of the Theological Education Study Program of the Catholic University of Indonesia Santu Paulus Ruteng. The activity partners are the people of the Church Base Community (CBC) Santu Padre Pio, Region II at Santa Maria Fatima Parish at Cancar in the Diocese of Ruteng. The main problems faced by partners are twofold: first, people are still experiencing anxiety/fear after the Covid-19 Pandemic and need spiritual strengthening; second, people need a facilitator for deepening the Bible during the National Scripture Month (NSM) 2022. Therefore, the Community Service Team became the answer to their problems by facilitating Scripture-deepening activities at BKSN and offering Bible-sharing activities that talk about God as the source of hope. The PkM activities were carried out in September 2022, coinciding with National Bible Month. The method used was sharing and catechesis. Activities are carried out with three main stages: preparation, implementation and evaluation. As results, the Scripture sharing and catechesis activities were completed, people gained knowledge about the Scriptures, made the Scriptures an inspiration to overcome their anxiety, and became an inspiration for new hope after the Covid-19 Pandemic. This community service activity recommends that sharing and catechesis activities be carried out more often